Competition and Custom in Economic Contracts: A Case Study of Illinois Agriculture. - Young, H; Burke, M (Department of Economics (Johns Hopkins University), 2000)
A customary contract is a set of terms that is standard in a given locale for a given economic purpose. Once established, such a standard tends to perpetuate itself because it creates expectations about what is fair and appropriate in a given type of economic bargain. We propose a dynamic model of how contractual customs form endogenously. Agents are situated in a geographical or social space, and they recontract periodically based on expected returns, local properties of the contract, and its conformity with local practice. The model predicts that the most likely geographic pattern consists of "patches" where contractual terms are nearly uniform, separated by bounderies where contractual norms jump from one set of terms to another. Differences in regional customs are roughly related to average differences in economic fundamentals, but they mask the considerable amount of heterogeneity that exists within regions. We compare these predictions with contractual practice in contemporary Illionois agriculture, and find considerable support for the model's prediction.